RELASI BAPA DAN ANAK PADA PERISTIWA SALIB MENURUT PANDANGAN JÜRGEN MOLTMANN - Thauwrisan, Lidya (Jurnal Amanat Agung, 2021)
Abstract: The cry of Jesus saying "My God, My God, why have You forsaken me?" draws Jürgen Moltmann’s attention to investigate what happened in the relationship between the Father and the Son at the event of the cross. Moltmann sees that in this event of the cross, for the first time, Jesus crying out called the Father not as Father but as "God". The exclamation is then seen as an indication of separation in the intratrinity relationship. Moltmann supports his conclusion with the thought of Karl Rahner who believes that "the immanent Trinity is the economic Trinity." In an attempt to explain what happened in the relationship between the Father and the Son at the cross, Moltmann uses the trinitarian point of view, namely seeing the Triune God first as three distinct persons and then seeing the unity. The weakness of Moltmann’s thinking is that it creates the impression that the economic Trinity can change the immanent Trinity and falls into the understanding of the social Trinity. This understanding can also give the impression that the cross event can separate the relationship between the Father and the Son. By using a descriptive analysis method, this paper will show that even in the event of the cross, the relationship between the Father and the Son remains intact and one. First of all, the author describes Moltmann’s view and provides some reviews of these views. Then, the author gives a view of the relationship between the Father and the Son with respect to the call of Jesus at the cross. Keywords: Jürgen Moltmann, broken Trinity, intratrinity relation, cross. Abstrak: Seruan Yesus yang mengatakan “Allahku, Allahku, mengapa Engkau meninggalkan Aku?” menarik perhatian Jürgen Moltmann untuk menyelidiki apa yang terjadi dalam relasi Bapa dan Anak pada peristiwa salib. Moltmann melihat bahwa pada momen ini untuk pertama kalinya Yesus berseru memanggil Bapa bukan dengan sebutan Bapa, tetapi dengan sebutan “Allah”. Seruan ini kemudian dilihat sebagai indikasi terjadinya keterpisahan dalam relasi intratritunggal. Moltmann mendukung pernyataannya ini dengan mengadopsi pemikiran Karl Rahner yang meyakini bahwa “the immanent Trinity is the economic Trinity.” Dalam upaya untuk menjelaskan apa yang terjadi dalam relasi Bapa dan Anak pada peristiwa salib, Moltmann memakai sudut pandang trinitaris, yaitu melihat Allah Tritunggal pertama-tama sebagai tiga pribadi yang berbeda kemudian melihat kesatuannya. Kelemahan dari pemikiran Moltmann adalah menimbulkan kesan the economic Trinity dapat mengubah the immanent Trinity dan jatuh pada pemahaman Trinitas sosial. Pemahaman ini juga dapat menimbulkan kesan bahwa peristiwa salib dapat membuat relasi Bapa dan Anak terpisah. Dengan menggunakan metode analisis deskriptif, tulisan ini akan memperlihatkan bahwa pada peristiwa salib pun, relasi Bapa dan Anak tetap utuh dan satu. Pertama-tama penulis memaparkan pandangan Moltmann dan memberikan beberapa tinjauan terhadap pandangan tersebut. Kemudian, penulis memberikan pandangan tentang relasi Bapa dan Anak terkait dengan seruan Yesus. Kata-kata Kunci: Jürgen Moltmann, keterpisahan Tritunggal, relasi intratritunggal, salib.